Perjanjian Kerja Sebagai Upaya P Perjanjian Kerja Sebagai Upaya Perlindungan serta Pemenuhan Hak-Hak Asasi Manusia untuk Pekerja Migran Indonesia: Perjanjian Kerja Sebagai Upaya Perlindungan serta Pemenuhan Hak-Hak Asasi Manusia untuk Pekerja Migran Indonesia - Jatmiko, Ludfie Jatmiko Setyo Poerwoko; Andi Fariana (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2025)
Human rights are natural that have been attached to individuals since birth and given directly by God Almighty and as a gift, World Health Organization has the right to education, health rights, employment rights, and so on. As is known, the dense population of Indonesia, increasing competition, and narrow employment and income are not as expected in addition to the growing daily needs of living, encouraging people to prefer to work abroad commonly referred to as Indonesian Migrant Workers (PMI). This fact, in fact, is not balanced by the government's ability to provide jobs that are able to absorb them. The narrowness of employment in the country has caused the lower society to turn to wider and more economically promising job opportunities abroad. On the other hand, the state is the party that is obliged to guarantee economic rights. This right is a human right today. This article discusses the concept of Employment Agreements as an Effort to Protect and Fulfill Human Rights for Indonesia Migran Workers.